Water-based intermediate coat composition with low-temperature stone impact resistance, water-based intermediate coat prepared from same and application of water-based intermediate coat composition

By using a water-based intra-based paint composition with a specific proportion of components such as aqueous polyurethane dispersion and amino resin in automotive coatings, the problem of insufficient stone-striking performance and humidity-striking resistance of automobile coatings under low temperature conditions is solved, and excellent low-temperature stone-striking resistance and humidity-striking resistance are achieved.

CN119639323APending Publication Date: 2025-03-18NIPPON PAINT CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311199355.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing automotive coatings have poor protection performance against gravel impacts under low temperature conditions (such as below -20℃), and their humidity and heat resistance are also insufficient.

Method used

An aqueous medium-coating composition is used, which comprises a specific proportion of aqueous polyurethane dispersions A and B, a methylated amino resin, a mixed etherified amino resin and a phosphate adhesion promoter. By combining these components, a coating with excellent low-temperature stone impact resistance and moisture and heat resistance is formed.

Benefits of technology

The water-based painted composition can significantly improve the stone-striking performance of the coating under low temperature conditions, and perform well in terms of hardness, adhesion and water resistance, meeting the demand of automotive coatings for harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004453519650000074
    Figure BDA0004453519650000074
  • Figure BDA0004453519650000081
    Figure BDA0004453519650000081
  • Figure BDA0004453519650000091
    Figure BDA0004453519650000091
Patent Text Reader

Abstract

The invention discloses a water-based intermediate coat composition with low-temperature stone impact resistance, water-based intermediate coat prepared from the water-based intermediate coat composition and application of the water-based intermediate coat composition. The water-based intermediate coat composition is prepared from the following components in parts by weight: 4 to 8 parts of water-based polyurethane dispersion A, 8 to 15 parts of water-based polyurethane dispersion B, 2 to 5 parts of methylated amino resin, 5 to 10 parts of mixed etherified amino resin and 0.2 to 0.4 part of phosphate adhesion promoter, wherein the hydroxyl value of the waterborne polyurethane dispersion A is lt; the acid value is 20-35 mgKOH / g, and the number-average molecular weight is gt; the particle size of the resin is 50-100nm, and the pH (Potential of Hydrogen) of the dispersion is 7.0-8.5; the hydroxyl value of the waterborne polyurethane dispersion B is 95-125 mgKOH / g, the particle size of the resin is 30-80 nm, and the pH value of the dispersion is 7.0-9.0.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of coatings, and more specifically to a water-based mid-coat paint composition with low-temperature stone chip resistance, a water-based mid-coat paint prepared therefrom, and applications thereof. Background Art

[0002] Waterborne automotive coatings are a type of multi-component material that uses water-emulsifiable, water-dispersible and water-soluble polymers as film-forming substances, water as the main dispersion medium, and organic solvents as co-solvents. As a product system that complies with the government's low volatile organic compound (low VOC) laws and regulations on coatings, and at the same time keeps up with the green and environmentally friendly trend favored by the general public, waterborne automotive coatings have been actively used and promoted by various automobile manufacturers in China since 2009.

[0003] In the traditional water-based three-coat-two-bake (3C2B) automotive coating system, the film thickness of the midcoat is about 30 to 40 microns, and a high-temperature baking of 140°C is required to achieve the curing and crosslinking of the midcoat, which results in a large amount of material and energy consumption. The water-based three-coat-one-bake (3C1B) coating system can further reduce the film thickness of the midcoat, and does not require high-temperature baking. It only needs to flash dry at room temperature for 4-8 minutes before the next step of color paint coating can be carried out. Therefore, the automotive painting line using the water-based three-coat-one-bake (3C1B) process can further reduce the consumption of coating materials, reduce the energy consumption of the baking process, and more effectively reduce VOC emissions during the painting process.

[0004] With the rapid development of national transportation infrastructure and the gradual increase in the popularity of automobiles, while bringing convenience to the general public and smooth logistics, it also puts forward higher requirements on the performance of automobile coatings. Among them, the more prominent problem is the resistance to low-temperature stone impact, that is, the protection performance of automobile coatings against the impact of granular foreign bodies such as gravel and sand under low temperature conditions (such as -20℃). At present, automobile coatings on the market have good defense effects against various impacts of gravel and sand under normal temperature conditions (20-25℃), and can meet the performance standards set by automobile manufacturers. However, considering the vast territory of my country, the terrain, road conditions and environmental climate of various places are obviously different; especially when vehicles are driving in the northern winter or high-altitude cold areas, due to the low ambient temperature (such as below -20℃), the film-forming resin in the automobile coating is prone to phase transition (high elastic state to glass state), the flexibility and adhesion of the paint film are reduced, and the brittleness is increased, which reduces the protective effect of the body coating against the impact of various gravel particles splashed by the road surface, making the coating near the impact point of the body prone to cracking and falling off, and causing rust damage to the steel substrate of the body. Therefore, automotive coating products with good stone impact resistance at room temperature often have unsatisfactory low-temperature stone impact resistance when facing low-temperature environments (such as below -20℃), and it is difficult to meet the performance requirements of actual use. Therefore, it is necessary to develop automotive coating products with excellent low-temperature (such as below -20℃) stone impact resistance from the perspective of product design innovation.

[0005] In addition to the low-temperature stone impact resistance, the moisture and heat resistance of the three-coat-one-bake automotive coating is also a focus that needs to be paid attention to. Compared with the traditional three-coat-two-bake coating, the three-coat-one-bake coating reduces the film thickness of the mid-coat paint coating and cancels the separate high-temperature baking and curing process of the mid-coat paint coating. While reducing the paint construction consumption, saving energy consumption and reducing VOC emissions, it also weakens the cross-linking density and buffering protection effect of the mid-coat paint coating film; it has an adverse effect on the moisture and heat resistance of the overall automotive coating. In addition, in order to improve the flexibility of the paint film under low temperature conditions (such as below -20°C) and improve the low-temperature stone impact resistance of the overall coating, the technology often tends to adopt the method of reducing the cross-linking density of the mid-coat paint coating and reducing the hardness of the paint film. This can certainly improve the low-temperature stone impact resistance to a certain extent, but it will further reduce the shielding and protection effect of the coating on the wet and hot water vapor in the external environment, causing the paint film to have defects such as blistering, wrinkling, rust spots or loss of gloss, and the moisture and heat resistance of the coating cannot meet the normal use requirements of the vehicle. Therefore, it is particularly necessary to develop a three-coat-one-bake automotive coating product that has excellent low-temperature stone impact resistance and takes into account the requirements of moisture and heat resistance. Summary of the invention

[0006] Based on the above problems, the purpose of the present invention is to provide a water-based mid-coat paint composition with low-temperature stone chip resistance, a water-based mid-coat paint prepared therefrom and its application. The composite coating film composed of the water-based mid-coat paint prepared from the water-based mid-coat paint composition and color paint, varnish, etc. not only has excellent low-temperature (such as -20°C and lower) stone chip resistance and moisture and heat resistance, but also performs well in hardness, adhesion, water resistance and other aspects.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In one aspect, the present invention provides a water-based mid-coat paint composition having low-temperature stone chip resistance, comprising the following components in parts by weight:

[0009] 4-8 parts of waterborne polyurethane dispersion A, 8-15 parts of waterborne polyurethane dispersion B, 2-5 parts of methyl etherified amino resin, 5-10 parts of mixed etherified amino resin and 0.2-0.4 parts of phosphate adhesion promoter;

[0010] in:

[0011] The aqueous polyurethane dispersion A has a hydroxyl value of <5 mgKOH / g, an acid value of 20-35 mgKOH / g, a number average molecular weight of >10000, a resin particle size of 50-100 nm, and a dispersion pH of 7.0-8.5;

[0012] The aqueous polyurethane dispersion B has a hydroxyl value of 95-125 mgKOH / g, a resin particle size of 30-80 nm, and a dispersion pH of 7.0-9.0.

[0013] Furthermore, the weight ratio of the resin solids in the aqueous polyurethane dispersion B to the aqueous polyurethane dispersion A is 1.5-2.5.

[0014] Furthermore, the weight ratio of the resin solids in the mixed etherified amino resin to the methyl etherified amino resin is 2.0-3.0.

[0015] Furthermore, the methyl etherified amino resin has an imino group content of 1.3-1.7 and a hydroxymethyl group content of 0.20-0.30.

[0016] Furthermore, the content of imino groups in the mixed etherified amino resin is 1.4-1.9, and the content of hydroxymethyl groups is 0.15-0.40.

[0017] Furthermore, in the mixed etherified amino resin, the ratio of the number of methoxymethyl groups to the number of butoxymethyl groups is 1.4-2.0.

[0018] The “imino group content” mentioned above refers to the average number of imino groups contained in each amino resin molecule; and the “hydroxymethyl group content” refers to the average number of hydroxymethyl groups contained in each amino resin molecule.

[0019] Furthermore, the phosphate adhesion promoter is selected from di(2-ethylhexyl) phosphate.

[0020] Furthermore, the composition further comprises, by weight: 8-13 parts of acrylic resin, 4-8 parts of water-based polyester resin, 20-40 parts of pigment and filler slurry, 4-6 parts of additives, 5-9 parts of film-forming solvent and 10-20 parts of water.

[0021] In another aspect, the present invention provides a water-based mid-coat paint, which is prepared from the water-based mid-coat paint composition as described above.

[0022] In another aspect, the present invention provides a composite coating, which is prepared from raw materials including the water-based mid-coat paint as described above by adopting a three-coat-one-bake coating process.

[0023] In another aspect, the present invention provides the use of the water-based intermediate coating as described above in a water-based three-coat-one-bake coating process for automobiles.

[0024] The beneficial effects of the present invention are as follows:

[0025] In the automotive water-based three-coat-one-bake mid-coat paint composition provided in the present invention, under the condition of containing both methyl etherified amino resin and mixed etherified amino resin, a low hydroxyl content (hydroxyl value <5 mgKOH / g) aqueous polyurethane dispersion A and a high hydroxyl content (hydroxyl value 95-125 mgKOH / g) aqueous polyurethane dispersion B are selected for matching, which helps to improve the low-temperature stone chip resistance, moisture and heat resistance and water resistance of the mid-coat paint prepared from the composition. In addition, in the mid-coat paint, by preferably selecting a proportion of methyl etherified amino resin and mixed etherified amino resin for matching, while providing the paint film with good hardness, water resistance, moisture and heat resistance and other properties, it can also give the paint film sufficient toughness and high yield strength even under low temperature conditions, thereby showing excellent low-temperature stone chip resistance. Furthermore, a certain amount of phosphate adhesion promoter can not only improve the interfacial adhesion between coatings, but also catalyze the cross-linking reaction between the polyurethane dispersion and the amino resin, thereby improving the tensile strength and cohesive strength of the coating film and enhancing the resistance of the film to external gravel impact at low temperatures. DETAILED DESCRIPTION

[0026] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0027] In order to overcome the stone chip resistance and moisture and heat resistance of water-based automobile paint films under low temperature conditions (such as -20°C or lower), so that the water-based automobile paint films can be better used in harsh environments, a specific embodiment of the present invention provides a water-based mid-coat paint composition with low-temperature stone chip resistance, and the water-based mid-coat paint composition comprises the following components by weight:

[0028] 4-8 parts of waterborne polyurethane dispersion A, 8-15 parts of waterborne polyurethane dispersion B, 2-5 parts of methyl etherified amino resin, 5-10 parts of mixed etherified amino resin and 0.2-0.4 parts of phosphate adhesion promoter;

[0029] in:

[0030] The aqueous polyurethane dispersion A has a hydroxyl value of <5 mgKOH / g, an acid value of 20-35 mgKOH / g, a number average molecular weight of >10000, a resin particle size of 50-100 nm, and a dispersion pH of 7.0-8.5;

[0031] The aqueous polyurethane dispersion B has a hydroxyl value of 95-125 mgKOH / g, a resin particle size of 30-80 nm, and a dispersion pH of 7.0-9.0.

[0032] In the water-based mid-coat paint composition, a water-based polyurethane dispersion A and a water-based polyurethane dispersion B with specific hydroxyl values ​​are combined, and a certain amount of methyl etherified amino resin, mixed etherified amino resin and phosphate adhesion promoter are matched, so that the composite coating paint film composed of the mid-coat paint and the color paint, varnish, etc. prepared by the water-based mid-coat paint composition is particularly suitable for the three-coat-one-bake process. The paint film not only has excellent low-temperature stone impact resistance and moisture and heat resistance, but also performs well in hardness, adhesion and water resistance.

[0033] In some examples, in the water-based mid-coat paint composition, the total weight of each component is 100 parts.

[0034] In some examples, the weight ratio of the resin solids in the aqueous polyurethane dispersion B to the aqueous polyurethane dispersion A is 1.5-2.5. Wherein, the weight of the resin solids in the dispersion = the amount of resin × the resin solid content (%). Under this condition, when the obtained mid-coat paint composition is used as a mid-coat to prepare a water-based automotive paint film, the obtained paint film has good low-temperature stone resistance, moisture and heat resistance, and water resistance, and can also meet the performance requirements such as hardness and adhesion. And if the weight ratio of the two is less than 1.5, the paint film at the coating interface is prone to peeling and falling off during the low-temperature stone resistance test of the overall coating, and the hardness, water resistance, and moisture and heat resistance may not meet the requirements; if the weight ratio of the two is greater than 2.5, the hardness of the overall coating is increased, but the flexibility of the paint film is reduced, and it is easy to brittle fracture after impact, and the impact resistance is deteriorated. During the low-temperature stone resistance test, there is a phenomenon that large pieces of the paint film are broken and broken and fall off. Preferably, the weight ratio of the resin solids in the aqueous polyurethane dispersion B to the aqueous polyurethane dispersion A is 1.5-2.1, 1.8-2.1, 1.91-2.06, etc.

[0035] For example, the aqueous polyurethane dispersion A may be prepared by reacting a material including polyester polyol, non-aromatic diisocyanate, and diol containing a carboxyl functional group.

[0036] In some examples, the aqueous polyurethane dispersion A is prepared by a method comprising the following steps:

[0037] Synthesize polyester polyols with a hydroxyl value of 25-75 mgKOH / g, an acid value of <1 mgKOH / g, and a number average molecular weight of 1500-4000;

[0038] Under nitrogen protection, the polyester polyol and the diol containing a carboxyl functional group are mixed and then reacted with a non-aromatic diisocyanate until the NCO equivalent reaches 800 to 1100; after neutralization, a polyurethane prepolymer is obtained;

[0039] Under the condition of nitrogen protection, the polyurethane prepolymer is subjected to a chain extension reaction to obtain the waterborne polyurethane dispersion A.

[0040] In a specific example, the preparation of the aqueous polyurethane dispersion A comprises the following steps:

[0041] (1) Synthesis and preparation of polyester polyols:

[0042] Under nitrogen protection, neopentyl glycol (7.5 parts), 1,6-hexanediol (38.5 parts), and 1,6-hexanediol (54 parts) were added to the reactor in sequence, and the temperature was raised to 120° C. until the raw materials melted;

[0043] After the raw materials are completely melted and mixed, the temperature is raised to 160°C with continuous stirring and maintained for 1 hour, and then the temperature is raised to 230°C for 5 hours; during the 230°C heat preservation process, the acid value is tested regularly until the acid value drops below 1 mgKOH / g;

[0044] The temperature is lowered to below 80°C to obtain polyester polyol;

[0045] The prepared polyester polyol has a hydroxyl value of 25 to 75 mgKOH / g, an acid value of <1 mgKOH / g, and a number average molecular weight of 1500 to 4000;

[0046] (2) Synthesis and preparation of polyurethane prepolymer:

[0047] Under nitrogen protection, the polyester polyol (34 parts) and the diol containing a carboxyl functional group (2.5 parts) prepared above were added to the reactor in sequence, and then stirred and heated to 80° C.;

[0048] Under the condition of maintaining the reaction temperature at 80°C, add non-aromatic diisocyanate (12 parts), and continue to react at 80°C until the NCO equivalent reaches 800-1100;

[0049] The temperature was lowered to 50° C., triethylamine (2 parts) was added for neutralization, and water (49.5 parts) was added after sufficient neutralization to obtain a polyurethane prepolymer (NCO terminated);

[0050] Exemplarily, the diol containing a carboxyl functional group is selected from dimethylol propionic acid (DMPA) and / or dimethylol butyric acid (DMBA).

[0051] Exemplarily, the non-aromatic diisocyanate is selected from one or more of isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), trimethylhexamethylene diisocyanate (TMDI) or dicyclohexylmethane diisocyanate (HMDI);

[0052] (3) Synthesis and preparation of waterborne polyurethane dispersion A:

[0053] Under nitrogen protection, the polyurethane prepolymer (83.2 parts), ethylenediamine (0.8 parts) and water (16 parts) prepared above were added to the reactor in sequence, and the mixture was stirred and heated to 60° C. for constant temperature reaction for 1 to 2 hours until the prepolymer chain extension reaction was completed;

[0054] The temperature was lowered to 40° C., and the mixture was filtered and discharged to obtain an aqueous polyurethane dispersion A.

[0055] The waterborne polyurethane dispersion A prepared by the method contains a large number of flexible long-chain aliphatic polyester segments in its molecular structure, which can effectively reduce the glass transition temperature (Tg) of the polymer resin, so that the resin can still be in a highly elastic state under low temperature conditions (such as -20°C or below). When the coating is impacted at high speed by external gravel under the above low temperature conditions or at room temperature, the flexibility of the paint film of the mid-coat coating can timely convert the energy generated by the impact into the deformation potential energy of the paint film for step-by-step dissipation, reducing the energy intensity transmitted to the electrophoretic paint coating below, thereby providing a good buffering and protective effect for the electrophoretic paint coating. At the same time, the molecular weight of polyurethane dispersion A is relatively high (number average molecular weight>10000), so that the resin itself also has a certain film-forming cohesive strength, which effectively prevents the deformation degree of the paint film from exceeding the cohesive strength of the resin itself during the dissipation of the impact energy, resulting in tearing or internal rupture of the mid-coat coating, resulting in the phenomenon of the paint film breaking and falling off.

[0056] In this embodiment, exemplary aqueous polyurethane dispersions B are selected from, but are not limited to, U2750 (purchased from Covestro (China) Co., Ltd.), U 2755 / 1 (purchased from Covestro (China) Co., Ltd.), etc.

[0057] The segments in the molecular chain structure of the waterborne polyurethane dispersion B are rigid polycarbonate or alicyclic polyester segments, which can provide the required hardness for the paint film. In addition, the polyurethane dispersion B has a high hydroxyl group content (hydroxyl value: 95-125 mgKOH / g), and can effectively react with the amino resin in a chemical cross-linking reaction during the coating baking and curing process to form a three-dimensional cross-linked network structure, thereby improving the water resistance, moisture and heat resistance, chemical resistance and other properties of the overall coating. At the same time, the presence of a large number of active groups such as hydroxyl groups in the polyurethane dispersion B is also conducive to the formation of chemical bonding, hydrogen bonding and van der Waals force connection points between the coating interfaces, thereby improving the adhesion between the coatings, effectively preventing the energy of the gravel impact from damaging the adhesion between the coating interfaces, and reducing the probability of the coating peeling off from the interface.

[0058] In some examples, the methyl etherified amino resin has an imino group content (imino group content: the average number of imino groups contained in each amino resin molecule) of 1.3-1.7, and a hydroxymethyl group content (hydroxymethyl group content: the average number of hydroxymethyl groups contained in each amino resin molecule) of 0.20-0.30. Exemplary methyl etherified amino resins include, but are not limited to, 325 (purchased from Allnex Resins (China) Co., Ltd.), 327 (purchased from Allnex Resins (China) Co., Ltd.) or 072 (purchased from BASF Applied Chemicals Co., Ltd.) or one or more thereof.

[0059] In some examples, the content of imino groups in the mixed etherified amino resin is 1.4-1.9, and the content of hydroxymethyl groups is 0.15-0.40; and / or the ratio of methoxymethyl groups to butoxymethyl groups in the mixed etherified amino resin is 1.4-2.0. Exemplary mixed etherified amino resins include but are not limited to those selected from 254 (purchased from Allnex Resins (China) Co., Ltd.), 211 (purchased from Allnex Resins (China) Co., Ltd.) or more.

[0060] In this embodiment, the methyl etherified amino resin and the mixed etherified amino resin can both react chemically with the hydroxyl groups on the molecular chain of polyurethane dispersion B to form a cross-linked network structure, giving the paint film properties such as hardness, water resistance, moisture and heat resistance, and chemical resistance. At the same time, the amino resins can also undergo self-polymerization reactions, and the resulting amino resin homopolymer can further improve the hardness of the paint film because it contains a large amount of rigid melamine hexacyclic ring structure in the molecular chain skeleton. The cross-linked network structure generated by the reaction of the amino resin and polyurethane dispersion B can also improve the overall tensile strength of the mid-coat paint coating film, further enhance the cohesive strength of the paint film, alleviate the damage to the internal structure of the paint film caused by the impact of gravel, and reduce the probability of the paint film falling off due to internal tearing.

[0061] In some examples, the weight ratio of the resin solids in the mixed etherified amino resin to the methyl etherified amino resin is 2.0-3.0.

[0062] Further studies have shown that the reaction activity and self-polymerization tendency of the methyl etherified amino resin are stronger than those of the mixed etherified amino resin. In order to ensure that the overall coating has good low-temperature stone chip resistance and coordinates and balances flexibility, stone chip resistance, hardness, water resistance and other properties, it is necessary to ensure that the weight ratio of the resin solids in the mixed etherified amino resin and the methyl etherified amino resin is within the range of 2.0-3.0 (resin solid weight = resin dosage × resin solid content (%)). If the weight ratio of the two is less than 2.0, the low-temperature stone chip resistance of the paint film will be significantly reduced; if the weight ratio of the two is greater than 3.0, it is not conducive to the improvement of the cohesive strength of the paint film, affecting the low-temperature stone chip resistance of the paint film, and at the same time, it will also have an adverse effect on the hardness, water resistance, moisture and heat resistance of the paint film. In addition, it will also lead to a decrease in the compatibility and stability between the coating components, thereby affecting the construction and application of the coating.

[0063] Preferably, the weight ratio of the resin solids in the mixed etherified amino resin to the methyl etherified amino resin includes but is not limited to 2.2-2.5, 2.29-2.50, 2.29-2.33, 2.33-2.50, etc.

[0064] In some examples, the phosphate adhesion promoter is selected from di(2-ethylhexyl) phosphate, for example, which can be purchased from Luoyang Zhongda Chemical Co., Ltd. The molecular structure of the di(2-ethylhexyl) phosphate contains a phosphate group at one end and two isooctane molecular chains at the other end. The phosphate group can improve the adhesion between the coating interfaces and inhibit the peeling and shedding between the coating interfaces when the gravel hits; at the same time, the phosphate group can also provide acidity, which plays a role in assisting the catalytic cross-linking reaction between the amino resin and the polyurethane dispersion B, and also contributes to the formation of the cross-linked network of the paint film. If the dosage of di(2-ethylhexyl) phosphate is too low, its improvement effect on low-temperature stone impact resistance is not obvious; when the dosage is too high, the low-temperature stone impact resistance is not further improved, but the moisture and heat resistance of the paint film and the stability of the coating tend to deteriorate.

[0065] In some examples, the composition further comprises, by weight: 8-13 parts of acrylic resin, 4-8 parts of water-based polyester resin, 20-40 parts of pigment and filler slurry, 4-6 parts of additives, 5-9 parts of film-forming solvent and 10-20 parts of water.

[0066] Exemplarily, the acrylic resin is selected from ACW-1011 (purchased from NOROO Automotive Coatings Co., Ltd.).

[0067] Exemplarily, the waterborne polyester resin is selected from one or more of WATERSOL NP-6100 (purchased from DIC Synthetic Resin (Zhongshan) Co., Ltd.) and WATERSOL NP-5300 (purchased from DIC Synthetic Resin (Zhongshan) Co., Ltd.).

[0068] In this embodiment, there is no specific requirement for the selection of pigment and filler slurry, and any pigment and filler slurry commonly used in the art can be used. Exemplarily, the pigment and filler slurry includes, but is not limited to, white slurry (pigment is titanium dioxide), talcum powder slurry (pigment is talcum powder), black slurry (pigment is carbon black), and yellow slurry (pigment is iron oxide yellow).

[0069] Exemplarily, the film-forming solvent is selected from one or more of ethylene glycol butyl ether, ethylene glycol hexyl ether, ethylene glycol isooctyl ether, diethylene glycol ethyl ether, diethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol butyl ether, dipropylene glycol methyl ether, dipropylene glycol dimethyl ether, ethanol, n-propanol, isopropanol, n-butanol or isooctyl alcohol.

[0070] Exemplarily, the additives include: 1.5-3.5 parts of rheological additives and 1.5-3.5 parts of defoaming agents.

[0071] Exemplarily, the rheological additive is selected from LAPONITE RD (purchased from BYK Chemical (China) Co., Ltd.), W2N (purchased from Leifus (Shanghai) Chemical Trading Co., Ltd.), AS1130 (purchased from BASF New Materials Co., Ltd.), P2100W (purchased from Deqian (Shanghai) Chemical Co., Ltd.), AQH-633E (purchased from Kusunoki Chemicals Co., Ltd.), AQH-810 (available from Kusunoki Chemicals Co., Ltd.) etc.

[0072] Exemplarily, the defoaming agent is selected from ST 2400 (purchased from BASF New Materials Co., Ltd.), 104BC (purchased from Evonik (China) Co., Ltd.), One or more of FOAMEX 805N (purchased from Evonik (China) Co., Ltd.), BYKETOL-WA (purchased from BYK Chemical (China) Co., Ltd.), BYK-011 (purchased from BYK Chemical (China) Co., Ltd.), etc.

[0073] According to a specific embodiment of the present invention, a method for preparing the water-based mid-coat paint composition as described above is provided, and the preparation method comprises the following steps:

[0074] The components are mixed to obtain the water-based intermediate coating composition.

[0075] According to another specific embodiment of the present invention, a water-based mid-coat paint is provided. The water-based mid-coat paint is prepared from the water-based mid-coat paint composition as described above.

[0076] According to another specific embodiment of the present invention, a composite coating is provided. The composite coating is prepared from raw materials including the water-based mid-coat paint as described above by adopting a three-coat-one-bake coating process.

[0077] Exemplarily, the preparation of the composite coating comprises the following steps:

[0078] 1) forming an electrophoretic paint coating on a substrate;

[0079] 2) applying the water-based intermediate coating to the surface of the electrophoretic paint coating, flash drying at room temperature, to form a first coating;

[0080] 3) applying the color paint on the surface of the first coating layer, dehydrating, and forming a second coating layer;

[0081] 4) Applying the clear varnish on the surface of the second coating layer, baking and curing, and forming the third coating layer.

[0082] Furthermore, in step 1), the method for forming the electrophoretic paint coating specifically comprises: depositing the electrodeposition coating composition (electrophoretic paint) on the substrate, and baking and curing at 160-190° C. to form the electrophoretic paint coating.

[0083] Furthermore, in step 3), the dehydration temperature is 60-80°C.

[0084] Furthermore, in step 4), the temperature of baking and curing is 130-150°C.

[0085] Furthermore, the flash drying refers to the process in which the volatile components in the coating composition applied to the surface of the previous coating gradually evaporate over a period of time under room temperature. The flash drying time is 2-20 minutes.

[0086] Furthermore, the substrate may be a metal substrate for automobiles, preferably a phosphating pre-treated steel plate.

[0087] According to another specific embodiment of the present invention, there is provided a use of the water-based intermediate coating as described above in a water-based three-coat-one-bake coating process for automobiles.

[0088] The technical solution of the present invention is described below in conjunction with some specific embodiments:

[0089] Preparation of water-based three-coat and one-bake paint (BC) for automobiles:

[0090] The formula components of the automotive water-based three-coat one-baking paint (BC) are shown in Table 1:

[0091] Table 1

[0092]

[0093]

[0094] In Table 1:

[0095] 6803, CYMEL 370N, and CYMEL 250 were purchased from Allnex Resins (Shanghai) Co., Ltd.;

[0096] UCOAT N-800 was purchased from Shanghai Nagase Trading Co., Ltd.;

[0097] ACW-1011 was purchased from NOROO Automotive Coatings Co., Ltd.;

[0098] The components of the effect pigment slurry include: 15 parts (by weight, the same below) of ALUMINIUM PASTE 06-0672N aluminum powder (purchased from Aika Special Effect Pigments Trading (Shanghai) Co., Ltd.), 7 parts of ALUMINIUM PASTE 7130N aluminum powder (purchased from Aika Special Effect Pigments Trading (Shanghai) Co., Ltd.), 6 parts of Automotive Rutile Fine White A-903D-SP pearlescent powder (purchased from CQV Co., Ltd.), 5 parts of Dazzling Blue A-781S blue pearlescent powder (purchased from CQV Co., Ltd.), 11 parts of LUBRIZOL 2062 (mixed alkyl / aryl phosphate, purchased from Lubrizol Specialty Chemicals Manufacturing (Shanghai) Co., Ltd.), 39 parts of ethylene glycol isooctyl ether, and 17 parts of diethylene glycol ethyl ether;

[0099] The blue pigment paste is selected from the NAPER WF series blue paste of Nippon Paint (China) Co., Ltd.;

[0100] AQH-810 was purchased from Kusunoki Chemicals Co., Ltd.;

[0101] BYKETOL-WA was purchased from BYK Chemical (China) Co., Ltd.;

[0102] SURFYNOL 440 was purchased from Evonik (China) Co., Ltd.;

[0103] ST 2400, AS1130 was purchased from BASF New Materials Co., Ltd.

[0104] The preparation process steps of the automotive water-based three-coat one-baking paint (BC) are as follows:

[0105] 1) Preparation of aluminum powder & pearlescent effect pigment slurry:

[0106] ALUMINIUM PASTE 06-0672N aluminum powder, ALUMINIUM PASTE 7130N aluminum powder, AutomotiveRutile Fine White A-903D-SP pearl powder, Dazzling Blue A-781S blue pearl powder, ethylene glycol isooctyl ether and diethylene glycol ethyl ether are soaked in a static state, and then stirred and mixed evenly under high-speed dispersion conditions, and then LUBRIZOL 2062 is added, and stirring is continued to form an aluminum powder & pearl powder effect pigment slurry in which aluminum powder & pearl powder are stably dispersed in a solvent.

[0107] 2) Preparation of water-based three-coat-one-bake water-based base paint (BC) for automobiles:

[0108] Will 6803, UCOAT N-800, ACW-1011, stir and mix; add the aluminum powder & pearlescent effect pigment slurry prepared above, stir for about 10 minutes to mix evenly; then add CYMEL 370N and CYMEL 250 in turn, stir at high speed for about 15 minutes to mix evenly; then add AQH-810, BYKETOL-WA, SURFYNOL 440 and ST 2400 and other additives, stir for about 10 minutes; continue to add isooctyl alcohol, ethylene glycol isooctyl ether and other solvents, stir for about 15 minutes; then add NAPER WF series blue paste and water; finally slowly add AS1130 rheological additive, after stirring for about 30 minutes, a uniformly mixed automotive water-based three-coat one-bake paint (BC) was obtained.

[0109] After the preparation of the paint BC product, dilute it with water to 160-180mPa.s (23°C, 250sec -1 ) Viscosity. The viscosity is measured by a rotary viscometer R-180, and the test method is: 23°C, 2# rotor / 2# sleeve, 1000sec -1 Shear rate, 180 seconds, then 250 seconds -1 shear rate, 60s.

[0110] Preparation example of midcoat:

[0111] Preparation of water-based three-coat-one-bake intermediate paint 1-18 (PR1-PR18) for automobiles:

[0112] The formula components of the automotive water-based three-coat-one-bake intermediate paint 1-18 (PR1-PR18) are shown in Table 2-Table 6:

[0113] Table 2

[0114]

[0115] Table 3

[0116]

[0117]

[0118] Table 4

[0119]

[0120] Table 5

[0121]

[0122]

[0123] Table 6

[0124]

[0125] In the above-mentioned mid-coat paint formula in Table 2-6:

[0126] The preparation method of waterborne polyurethane dispersion A is as follows:

[0127] (1) Synthesis and preparation of polyester polyols:

[0128] Under nitrogen protection, 7.5 parts of neopentyl glycol, 38.5 parts of 1,6-hexanediol, and 54 parts of 1,6-adipic acid were added to the reactor in sequence, and the temperature was raised to 120° C. until the raw materials melted;

[0129] After the raw materials are completely melted and mixed, the temperature is raised to 160°C with continuous stirring and maintained for 1 hour, and then the temperature is raised to 230°C for 5 hours; during the 230°C heat preservation process, the acid value is tested regularly until the acid value drops below 1 mgKOH / g;

[0130] The temperature is lowered to below 80°C to obtain polyester polyol;

[0131] The prepared polyester polyol has a hydroxyl value of 25-75 mgKOH / g, an acid value of less than 1 mgKOH / g and a number average molecular weight of 1500-4000.

[0132] (2) Synthesis and preparation of polyurethane prepolymer:

[0133] Under nitrogen protection, 34 parts of the polyester polyol prepared above and 2.5 parts of dimethylol propionic acid (DMPA) were added to the reactor in sequence, and then stirred and heated to 80° C.;

[0134] While maintaining the reaction temperature at 80°C, add 12 parts of isophorone diisocyanate (IPDI) and continue to react at 80°C until the NCO equivalent reaches 800-1100;

[0135] The temperature was lowered to 50° C., 2 parts of triethylamine were added for neutralization, and after sufficient neutralization, 49.5 parts of water were added to obtain a polyurethane prepolymer (NCO terminated).

[0136] (3) Synthesis and preparation of waterborne polyurethane dispersion A:

[0137] Under nitrogen protection, 83.2 parts of the polyurethane prepolymer prepared above, 0.8 parts of ethylenediamine, and 16 parts of water were added to the reactor in sequence, and the mixture was stirred and heated to 60° C. for constant temperature reaction for 1-2 hours until the prepolymer chain extension reaction was completed;

[0138] The temperature was lowered to 40° C., and the mixture was filtered and discharged to obtain an aqueous polyurethane dispersion A.

[0139] The prepared aqueous polyurethane dispersion A has a solid content of 32%-36%, a hydroxyl value of <5 mgKOH / g, an acid value of 20-35 mgKOH / g, a number average molecular weight of >10000, a resin particle size of 50-100 nm, and a dispersion pH of 7.0-8.5.

[0140] U 2755 / 1 is a waterborne polyurethane dispersion purchased from Covestro (China) Co., Ltd., with a solid content of 34%-36%, a hydroxyl value of 95-110 mgKOH / g, a resin particle size of 30-60 nm, and a dispersion pH of 7.0-9.0.

[0141] PU 1328W is a waterborne polyurethane dispersion purchased from BASF (China) Co., Ltd., with a solid content of 34%-36%, a hydroxyl value of 25-35 mgKOH / g, and a dispersion pH of 9.5-10.5.

[0142] U 2757 is a waterborne polyurethane dispersion purchased from Covestro (China) Co., Ltd., with a solid content of about 50%-55%, a hydroxyl value of 50-70 mgKOH / g, an acid value of <10 mgKOH / g, a resin particle size of 90-120 nm, and an emulsion pH of 7.0-8.5.

[0143] 325 is a methyl etherified amino resin purchased from Allnex Resins (China) Co., Ltd., with a solid content of 78%-82%, an imino group content (imino group content: the average number of imino groups contained in each amino resin molecule) of 1.4-1.6, and a hydroxymethyl group content (hydroxymethyl group content: the average number of hydroxymethyl groups contained in each amino resin molecule) of 0.20-0.25.

[0144] 254 is a mixed etherified amino resin purchased from Allnex Resins (China) Co., Ltd., with a solid content of 78%-82%, an imino group content of 1.4-1.6, a hydroxymethyl group content of 0.15-0.22, and a ratio of methoxymethyl groups to butoxymethyl groups of 1.5-1.8.

[0145] 303 is a methyl etherified amino resin purchased from Allnex Resins (China) Co., Ltd., with a solid content of ≥98%, an imino group content of 0.05-0.1, and a hydroxymethyl group content of 0.2-0.3.

[0146] 251 is a mixed etherified amino resin purchased from Allnex Resins (China) Co., Ltd., with a solid content of 78%-82%, an imino group content of 0.5-0.9, a hydroxymethyl group content of 0.7-1.0, and a ratio of methoxymethyl groups to butoxymethyl groups of 0.6-0.9.

[0147] WATERSOL NP-6100 is a water-based polyester resin purchased from DIC Synthetic Resin (Zhongshan) Co., Ltd.

[0148] Di(2-ethylhexyl) phosphate was purchased from Luoyang Zhongda Chemical Co., Ltd.

[0149] LUBRIZOL 2062 is a mixed alkyl / aryl phosphate ester purchased from Lubrizol Specialty Chemical Manufacturing (Shanghai) Co., Ltd.

[0150] TEGO FOAMEX 805N was purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.

[0151] NAPER WF CR-97 white paste is selected from NAPER WF series white paste of Nippon Paint (China) Co., Ltd.; its formula components include: 70 parts of TIPAQUE CR-97 titanium dioxide (purchased from Ishihara Sangyo Co., Ltd.), 8 parts of DISPERBYK-190 dispersant (purchased from BYK Chemical (China) Co., Ltd.), and 22 parts of water.

[0152] According to the formula component information of the mid-coat paint composition listed in Table 2 to Table 6 and the solid content of each resin component, P1 and P2 in the mid-coat paint 1-18 (PR1-PR18) can be further calculated.

[0153] Specifically, P1 refers to the aqueous polyurethane dispersion B in the mid-coat paint composition (selected in the preparation example is U 2755 / 1, or U 2757) and polyurethane dispersion A (or PU1328W) by weight of resin solids (resin solids weight = resin dosage × resin solid content (%)); P2 refers to the mixed etherified amino resin in the mid-coat paint composition (selected in the preparation example is 254, or 251) and methyl etherified amino resin (selected in the preparation example is 325, or 303) by weight ratio of resin solids.

[0154] The calculation results of P1 and P2 in mid-coat paints 1-18 (PR1-PR18) are shown in Table 7 below.

[0155] Table 7

[0156]

[0157] The preparation process steps of the automotive water-based three-coat-one-bake intermediate paint 1-18 (PR1-PR18) are as follows:

[0158] 1) Preparation of NAPER WF CR-97 white pulp

[0159] After mixing TIPAQUE CR-97 titanium dioxide, DISPERBYK-190 dispersant, water, etc. in advance, add grinding beads such as glass beads or zirconium beads in a sand mill, grind and disperse until the fineness reaches less than 5 microns to obtain NAPER WF CR-97 white slurry;

[0160] 2) Preparation of water-based three-coat-one-bake intermediate paint 1-18 (PR1-PR18) for automobiles

[0161] Under stirring conditions, polyurethane dispersion A (or PU 1328W), U 2755 / 1(or U 2757), WATERSOL NP-6100, stir for about 10 minutes to mix evenly; then add ethylene glycol butyl ether and continue stirring for about 10 minutes; then add ACW-1011, 325 (or 303), 254 (or 251), stirring for about 20 minutes; then continue to add TEGO FOAMEX 805N, BYKETOL-WA, After adding AQH-810 and di(2-ethylhexyl) phosphate and other additives, stir for about 15 minutes; then add ethylene glycol isooctyl ether, isooctyl alcohol, and water; finally, slowly add AS1130 rheological additive, after stirring for about 30 minutes, a uniformly mixed automotive water-based three-coat-one-bake intermediate paint 1-18 (PR1-PR18) was obtained.

[0162] After the preparation of the intermediate coating 1-18 (PR1-PR18), dilute with water to 150-170 mPa.s (23°C, 250 sec -1 ) Viscosity. The viscosity is measured by a rotary viscometer R-180, and the test method is: 23°C, 2# rotor / 2# sleeve, 1000sec -1 Shear rate, 180 seconds, then 250 seconds -1Shear rate, 60s.

[0163] Application Examples

[0164] Comparative Examples 1-15

[0165] The spraying plate making method of Comparative Examples 1-15 of the present invention is as follows:

[0166] Electrophoretic paint PN-310 (from Nippon Paint (China) Co., Ltd.) was applied on the surface of the passivated steel plate treated with zinc phosphate, and the required substrate plate was prepared after baking at 160°C for 30 minutes (the dry film thickness of the electrophoretic paint coating was 19-24 μm).

[0167] A LACTEC automatic spraying robot with a DURR atomizer is used for spraying: the aforementioned midcoat (the aforementioned automotive water-based three-coat and one-bake midcoat: PR2-7, PR9-14, PR16-18) is first sprayed on the surface of the substrate plate, and flashed for 5 minutes at room temperature 21-24°C and humidity 65±5% RH; then the first color paint (the aforementioned automotive water-based three-coat and one-bake color paint: BC) is sprayed, and flashed for 2 minutes at room temperature 21-24°C and humidity 65±5% RH; then the second color paint (the aforementioned automotive water-based three-coat and one-bake color paint: BC) is sprayed, and flashed for 2 minutes at room temperature 21-24°C and humidity 65±5% RH; then the above sample (substrate plate / midcoat / color paint) is pre-baked in an oven at 80°C for 8 minutes, the pre-baked sample is taken out, and cooled to room temperature 21-24°C. Next, a varnish mixture (varnish: PUE O-1200 varnish, curing agent: H-1200 curing agent, varnish: curing agent = 100:40 (weight ratio); both varnish and curing agent are from Nippon Paint (China) Co., Ltd.) was sprayed on the surface of the sample, and flash-dried for 8 minutes at room temperature 21-24°C and humidity 65±5% RH; finally, the prepared sample (substrate plate / midcoat / color paint / varnish) was placed in an oven and baked at 140°C for 30 minutes; the baked sample was taken out and cooled to room temperature 21-25°C.

[0168] For the test of coating film performance, the dry film thickness of each coating of the prepared sample (substrate plate / midcoat / color paint / clear coat) is: midcoat coating: 18-23 microns, first color paint coating: 6-8 microns, second color paint coating: 6-8 microns, clear coat: 35-45 microns.

[0169] Specifically, the coating structures (mid-coat / color paint / clear varnish) of Comparative Examples 1-15 are shown in Table 8 below.

[0170] Table 8

[0171]

[0172]

[0173] Examples 1-3

[0174] The spraying plate making method of the present embodiment 1-3 is the same as the above-mentioned comparative example 1-15, the only difference being that the mid-coat paint used (the aforementioned automotive water-based three-coat and one-bake mid-coat paint: PR2-7, PR9-14, PR16-18) is replaced with another mid-coat paint (the aforementioned automotive water-based three-coat and one-bake mid-coat paint: PR1, PR8, PR15).

[0175] Specifically, the coating structures (midcoat / color paint / clear coat) of Examples 1-3 are shown in Table 9:

[0176] Table 9

[0177]

[0178] Coating film performance test

[0179] Low temperature stone impact resistance test:

[0180] Precool the sample (substrate plate / midcoat / color paint / clear coat) to -25°C in a refrigerator, then fix it on the sample holder inside the chamber of the SUGA JA-400LAZ stone impact tester, set the temperature of the holder back plate to -20°C, and ensure that the temperature of the sample can be maintained at around -20°C during the stone impact test. Add 250g of M2 nut to the launch cabin of the JA-400LAZ stone impact tester and close the cabin cover, then open the compressed air valve, and impact the nut onto the sample surface with a pressure of 0.49Mpa, with the impact direction and the angle between the sample and the sample being 45°.

[0181] After the impact is completed, remove the sample and remove all the paint film debris on the sample coating surface with Tesa 4657 tape. Then check the degree of damage on the paint film surface, and judge the low-temperature stone impact test results of the sample coating based on the area ratio of the paint film peeling off on the sample coating surface and the diameter of the maximum paint film peeling point.

[0182] Note: The low-temperature stone impact resistance results are divided into 10 levels, among which the paint film shedding area ratio of level 1 is ≤3%, and the maximum peeling point diameter is ≤1.5mm; the paint film shedding area ratio of level 5 is 12%-15%, and the maximum peeling point diameter is 3.0-3.5mm; the paint film shedding area ratio of level 10 is >80%, and the maximum peeling point diameter is >8.0mm.

[0183] Adhesion test:

[0184] The test method and result grade of adhesion were conducted in accordance with GB / T 9286. A rigid blade cutter with a V-shaped blade was selected, the number of cuts in each direction of the grid pattern was 6, and the cutting spacing was 2 mm.

[0185] Hardness test:

[0186] The hardness test method and result grade evaluation are carried out in accordance with GB / T 6739. The pencils used are "Zhonghua" drawing pencils.

[0187] Water resistance test:

[0188] The water resistance test method is carried out in accordance with GB 5209 standard.

[0189] Soak the sample (substrate board / midcoat / color paint / clear varnish) in deionized water at a constant temperature of 40±1℃ for 240 hours. Take it out and observe whether the paint film on the surface of the sample has defects such as blistering, gloss loss, rust spots, etc., and test the adhesion.

[0190] The test method and result grade of adhesion are as described above.

[0191] Moisture and heat resistance test:

[0192] The test method for moisture and heat resistance is carried out in accordance with GB / T 1740 standard.

[0193] Place the sample (substrate board / midcoat / color paint / clear varnish) in a constant temperature and humidity chamber (47±1℃, 96±2% relative humidity) for 240 hours, take it out and observe whether the paint film on the surface of the sample has defects such as blistering, gloss loss, rust spots, etc., and test the adhesion.

[0194] The test method and result grade of adhesion are as described above.

[0195] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 1-2 and Example 1 of the present invention are shown in Table 10:

[0196] Table 10

[0197] By comparing and analyzing the data in Table 10, it can be obtained that Example 1 can meet the requirements in terms of the tested low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 1 fails to meet the requirements in terms of low-temperature stone chip resistance, hardness, water resistance, and moisture and heat resistance, and Comparative Example 2 fails to meet the requirements in terms of low-temperature stone chip resistance. The main reason is that the waterborne polyurethane dispersion A and polyurethane dispersion B in the intermediate coating formula components of Comparative Example 1 / Comparative Example 2 (the embodiment and the comparative example are selected as The weight percentage range of the formula of XP 2755 / 1) does not conform to the range required by the present invention, and cannot achieve good coordination and balance between the low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.) of the coating film.

[0198] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 3-4 and Example 1 of the present invention are shown in Table 11:

[0199] Table 11

[0200]

[0201]

[0202] By comparing and analyzing the data in Table 11, it can be obtained that Example 1 can meet the requirements in terms of low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 3 fails to meet the requirements in terms of low-temperature stone chip resistance, and Comparative Example 4 fails to meet the requirements in terms of low-temperature stone chip resistance and water resistance. The main reason is that the P1 value (polyurethane dispersion B (the selected in the embodiment and the comparative example) in the intermediate coating formula components of Comparative Example 3 / Comparative Example 4 is The weight ratio of the resin solids of polyurethane dispersion A (U 2755 / 1) to polyurethane dispersion A) is not in line with the scope required by the present invention, and the coating film cannot achieve good coordination and balance between low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.).

[0203] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 5-6 and Example 1 of the present invention are shown in Table 12:

[0204] Table 12

[0205]

[0206] By comparing and analyzing the data in Table 12, it can be obtained that Example 1 can meet the requirements in terms of low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 5 fails to meet the requirements in terms of low-temperature stone chip resistance, and Comparative Example 6 fails to meet the requirements in terms of low-temperature stone chip resistance, hardness, and moisture and heat resistance. The main reason is that the waterborne polyurethane dispersion A is replaced in the intermediate coating formulation components of Comparative Example 5. PU 1328W resin, and polyurethane dispersion B in the intermediate coating formulation component of Comparative Example 6 (selected in Comparative Example 6 is U 2757), the hydroxyl value range of the resin does not conform to the range required by the present invention, and the coating film cannot achieve good coordination and balance between low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.).

[0207] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 7-8 and Example 2 of the present invention are shown in Table 13:

[0208] Table 13

[0209]

[0210]

[0211] By comparing and analyzing the data in Table 13, it can be obtained that Example 2 can meet the requirements in terms of low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 7 fails to meet the requirements in terms of low-temperature stone chip resistance, and Comparative Example 8 fails to meet the requirements in terms of low-temperature stone chip resistance, hardness, water resistance, and moisture and heat resistance. The main reason is that the methyl etherified amino resin in the intermediate coating formula components of Comparative Example 7 / Comparative Example 8 (the selected 325) and mixed etherified amino resin (selected in the embodiments and comparative examples is 254) does not conform to the range required by the patent of the present invention, and fails to achieve good coordination and balance between low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.) of the coating film.

[0212] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 9-10 and Example 2 of the present invention are shown in Table 14:

[0213] Table 14

[0214]

[0215] By comparing and analyzing the data in Table 14, it can be obtained that Example 2 can meet the requirements in terms of the tested low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 9 fails to meet the requirements in terms of low-temperature stone chip resistance and water resistance, and Comparative Example 10 fails to meet the requirements in terms of low-temperature stone chip resistance. The main reason is that the P2 value ( 254 and 325 weight ratio of resin solids) is inconsistent with the scope required by the patent of this invention, and cannot achieve good coordination and balance between low-temperature stone impact resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.) of the coating film.

[0216] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 11-12 and Example 2 of the present invention are shown in Table 15:

[0217] Table 15

[0218]

[0219] By comparing and analyzing the data in Table 15, it can be obtained that Example 2 can meet the requirements in terms of low-temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance, while Comparative Example 11 fails to meet the requirements in terms of low-temperature stone chip resistance, hardness, water resistance, and moisture and heat resistance, and Comparative Example 12 fails to meet the requirements in terms of low-temperature stone chip resistance. The main reason is that the methyl etherified amino resin in the intermediate coating formula component of Comparative Example 11 (Comparative Example 11 is selected as 303), and the mixed etherified amino resin in the coating formulation component of Comparative Example 12 (the selected 251), the structural parameters of the resin (imino group content, hydroxymethyl group content, and the ratio of methoxymethyl groups to butoxymethyl groups) are inconsistent with the scope required by the present invention, and the coating film is unable to achieve good coordination and balance between low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.).

[0220] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Examples 13-14 and Example 3 of the present invention are shown in Table 16:

[0221] Table 16

[0222]

[0223]

[0224] By comparing and analyzing the data in Table 16, it can be obtained that Example 3 can meet the requirements in the tested low-temperature stone chip resistance, adhesion, hardness, water resistance, moisture and heat resistance, etc., while Comparative Example 13 fails to meet the requirements in low-temperature stone chip resistance, and Comparative Example 14 fails to meet the requirements in low-temperature stone chip resistance, moisture and heat resistance, etc. The main reason is that the formula weight percentage range of the phosphate adhesion promoter (di(2-ethylhexyl) phosphate is selected in the embodiment and the comparative example) in the intermediate coating formula components of Comparative Example 13 / Comparative Example 14 does not conform to the range required by the patent of the present invention, and the coating film cannot achieve good coordination and balance between low-temperature stone chip resistance and other properties (such as hardness, water resistance, moisture and heat resistance, etc.).

[0225] The test results of the coating film properties (low temperature stone chip resistance, adhesion, hardness, water resistance, and moisture and heat resistance) of Comparative Example 15 and Example 3 of the present invention are shown in Table 17:

[0226] Table 17

[0227]

[0228] By comparing and analyzing the data in Table 17, it can be obtained that Example 3 can meet the requirements in terms of the tested low-temperature stone chip resistance, adhesion, hardness, water resistance, moisture and heat resistance, etc., while Comparative Example 15 fails to meet the requirements in terms of low-temperature stone chip resistance. The main reason is that the phosphate adhesion promoter in the intermediate coating formula component of Comparative Example 15 (Comparative Example 15 selects LUBRIZOL 2062 (mixed alkyl / aryl phosphate)) does not meet the scope required by this patent, and the low-temperature stone chip resistance of its coating film fails to meet the required performance standard requirements.

[0229] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A water-based mid-coat paint composition having low-temperature stone chip resistance, characterized in that: By weight, it contains the following components: 4-8 parts of waterborne polyurethane dispersion A, 8-15 parts of waterborne polyurethane dispersion B, 2-5 parts of methyl etherified amino resin, 5-10 parts of mixed etherified amino resin and 0.2-0.4 parts of phosphate adhesion promoter; in: The aqueous polyurethane dispersion A has a hydroxyl value of <5 mgKOH / g, an acid value of 20-35 mgKOH / g, a number average molecular weight of >10000, a resin particle size of 50-100 nm, and a dispersion pH of 7.0-8.5; The aqueous polyurethane dispersion B has a hydroxyl value of 95-125 mgKOH / g, a resin particle size of 30-80 nm, and a dispersion pH of 7.0-9.

0.

2. The water-based mid-coat paint composition according to claim 1, characterized in that: The weight ratio of the resin solids in the aqueous polyurethane dispersion B to the aqueous polyurethane dispersion A is 1.5-2.

5.

3. The water-based mid-coat paint composition according to claim 1, characterized in that: The weight ratio of the resin solids in the mixed etherified amino resin to the methyl etherified amino resin is 2.0-3.

0.

4. The water-based mid-coat paint composition according to claim 1, characterized in that: The methyl etherified amino resin has an imino group content of 1.3-1.7 and a hydroxymethyl group content of 0.20-0.

30.

5. The water-based mid-coat paint composition according to claim 1, characterized in that: The mixed etherified amino resin has an imino group content of 1.4-1.9 and a hydroxymethyl group content of 0.15-0.40; and / or In the mixed etherified amino resin, the ratio of the number of methoxymethyl groups to the number of butoxymethyl groups is 1.4-2.

0.

6. The water-based mid-coat paint composition according to claim 1, characterized in that: The phosphate adhesion promoter is selected from di(2-ethylhexyl) phosphate.

7. The water-based mid-coat paint composition according to claim 1, characterized in that: The composition further comprises, by weight: 8-13 parts of acrylic resin, 4-8 parts of water-based polyester resin, 20-40 parts of pigment and filler slurry, 4-6 parts of auxiliary agent, 5-9 parts of film-forming solvent and 10-20 parts of water.

8. A water-based mid-coat paint, characterized in that: The invention is prepared from the water-based mid-coat paint composition as described in any one of claims 1 to 7.

9. A composite coating, characterized in that: The water-based intermediate coating material is prepared by using a three-coating and one-baking coating process from raw materials comprising the water-based intermediate coating material as claimed in claim 8.

10. Use of the water-based intermediate coating as claimed in claim 8 in a water-based three-coat-one-bake coating process for automobiles.

Citation Information

Cited By

  • Water-based intermediate paint capable of resisting high and low temperature circulation for vehicle body and preparation and coating methods of water-based intermediate paint

    CN121673932A